Low Oxygen Concentrations Inhibit Trophoblast Cell Invasion from Early Gestation Placental Explants via Alterations in Levels of the Urokinase Plasminogen Activator System - LASH, Gendie E; OTUN, Harry A; INNES, Barbara A; BULMER, Judith N; SEARLE, Roger F; ROBSON, Stephen C (Biology of reproduction, 2006)
Extravillous trophoblast cell (EVT) invasion in early pregnancy occurs in a relatively low-oxygen environment. The role of oxygen in regulation of EVT invasion remains controversial. We hypothesized that 1) culture in 3% oxygen inhibits EVT invasion compared with culture at 8% or 20% oxygen and 2) inhibition of invasion is due to alterations in levels of components of the urokinase plasminogen activator (PLAU, uPA) system rather than through increased apoptosis and/or decreased proliferation. Placental samples (8â10, 12â14, and 16â20 wk gestation) were obtained from women undergoing elective surgical termination of pregnancy or after cesarean section delivery (term) at the Royal Victoria Infirmary, Newcastle upon Tyne, U.K. EVT invasion from placental explants cultured at 3%, 8%, or 20% oxygen was assessed using Matrigel invasion assays. Invasion was assessed on Day 6, explants were harvested for analysis of apoptosis and proliferation, and medium was stored for analysis of PLAU system components by ELISA and casein zymography. Culture at 3% oxygen inhibited EVT invasion. PLAU receptor and plasminogen activator inhibitor-2 protein levels were increased and PLAU activity decreased in these cultures. There was no difference in the proliferation in explants cultured at the three different oxygen concentrations. Apoptosis, assessed by M30 immunostaining, was increased in EVT at both 3% and 8% oxygen. The reduction in the invasive capacity of EVT cultured at 3% oxygen appears to be mediated both by a general inhibition of the PLAU system and a decrease in the number of cells available to invade. Abstract Invasion of primary first-trimester extravillous trophoblast cells is inhibited by culture in 3% oxygen via a mechanism associated with a decrease in the activity of the urokinase plasminogen activator system.